Nano-composite amine liquid decarburizing agent and preparation method thereof
By adding nano-level zirconia and lithium oxide to the amine liquid decarbonizer and optimizing its morphology and dispersion, the problem of insufficient efficiency and stability of traditional amine liquid decarbonizer in industrial waste gas treatment is solved, and a higher level of decarbonization selectivity and economicality.
Patent Information
- Application Number
- CN202311046152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
Traditional amine liquid decarbonizers have problems such as strong corrosiveness, foaming and degradation in industrial waste gas treatment, resulting in problems with their efficiency and stability during use.
The nanocomposite amine liquid decarburizer is formed by adding nano-scale zirconium oxide and lithium oxide to the amine liquid and optimizing its morphology and dispersion through a specific post-treatment process.
It significantly improves the corrosion resistance, foam resistance and oxidation resistance of the amine liquid decarbonizer, enhances its absorption and regeneration efficiency, improves the selectivity and stability of decarbonization, and reduces energy consumption and costs.
Abstract
Description
Technical Field
[0001] The technical field involved in this article is environmental protection and new materials. Specifically, the selectivity and stability of amine liquid decarbonizers used in industrial waste gas treatment are improved and optimized by utilizing the characteristics of nanocomposites to improve their decarbonization selectivity and stability. Background Art
[0002] In the industrial production process, waste gas emission is an important environmental issue. In order to reduce the emission of harmful gases such as carbon dioxide, amine liquid decarbonizer is widely used in industrial waste gas treatment. However, amine liquid decarbonizer itself has some disadvantages, such as strong corrosiveness, easy foaming, easy degradation, etc., which leads to problems with its efficiency and stability during use.
[0003] Nanocomposites are a new type of material with great application potential. By combining nanoscale materials with other materials, materials with new properties and functions can be produced. Adding nanocomposites to amine decarburizers can improve their performance and stability. For example, carbon nanotube / polymer composites can enhance the corrosion resistance, foaming resistance and oxidation resistance of amine decarburizers, and improve their absorption and regeneration efficiency. In addition to carbon nanotubes, nanocomposites such as metal oxides, silicate clays, and graphene can also be added to amine decarburizers. Factors such as the amount, morphology, and distribution of these nanocomposites will have different effects on the performance and stability of amine decarburizers, so specific optimization is required.
[0004] The present invention provides a method for improving the decarbonization selectivity and stability of an amine liquid decarbonizer by adding a nanocomposite material to the amine liquid decarbonizer. The innovation of the present invention is that the physicochemical properties of the amine liquid decarbonizer can be optimized by using a nanocomposite material with a specific morphology and dispersibility, and the absorption and regeneration efficiency can be improved. The method provided by the present invention can improve the decarbonization selectivity and stability of the amine liquid decarbonizer, thereby effectively reducing the emission of harmful gases such as carbon dioxide in industrial production. Summary of the invention
[0005] The invention provides a novel nano composite amine liquid decarbonizing agent and a preparation method thereof, which is intended to improve the performance and stability of the amine liquid decarbonizing agent.
[0006] Compared with traditional amine liquid decarbonizers, this decarbonizer has the following advantages: First, the addition of nanocomposite materials can significantly improve the corrosion resistance, oxidation resistance and foaming resistance of amine liquid decarbonizers, thereby improving their service life and stability. Secondly, this nanocomposite amine liquid decarbonizer can improve decarbonization selectivity and absorption efficiency, while reducing energy consumption and costs, and improving decarbonization efficiency and economy. In addition, this decarbonizer also has the special properties of nanomaterials, such as large surface area, good dispersibility, high reactivity, etc., which can meet the needs of different industrial scenarios and has broad application prospects.
[0007] Based on the above characteristics and advantages, this new type of nano-composite amine liquid decarbonizer can be widely used in waste gas treatment in industrial fields such as steel, chemical industry, and electric power. In addition to the industrial field, the decarbonizer can also be used in environmental protection, energy development and other fields, with broad application prospects and market value. Therefore, the development and application of the decarbonizer has important social significance.
[0008] The main technical idea of the present invention is to add nano-scale zirconium oxide and lithium oxide into the amine solution to make it have a specific form and dispersibility, thereby improving the performance and stability of the amine solution decarbonizer.
[0009] The present invention is achieved in that: The specific implementation method is as follows: A nano composite amine liquid decarbonizing agent, characterized in that it comprises the following components: a. Amine substances; b. Nano-sized zirconium oxide, with a particle size between 10 and 50 nm; c. Nano-scale lithium oxide, with a particle size between 10 and 50 nm; d. surfactant; e. Auxiliary additives.
[0010] The amine substances include but are not limited to alcohol amines, ether amines, amides, cyclic amines and the like.
[0011] The surfactant includes but is not limited to sodium dodecylbenzene sulfonate and the like.
[0012] The auxiliary additives include but are not limited to sodium chloride, potassium chloride and the like.
[0013] The mass ratio of the nano-scale zirconium oxide to lithium oxide is 1:2-3, and the added amount of the two is 0.1-0.5 wt% of the total amount of the decarburizer.
[0014] The added amount of the surfactant is 0.01-0.05 wt % of the total amount of the decarbonizing agent.
[0015] The amount of the auxiliary additive added is 0.1-0.5 wt% of the total amount of the decarburizer.
[0016] The nano composite amine liquid decarbonizing agent of the present invention has a viscosity of 20-100 mPa·s and a solubility in water of 20-35wt%.
[0017] The present invention also provides a method for preparing a nano composite amine liquid decarbonizing agent, which mainly comprises the following steps: a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: dissolving zirconium acetate and lithium acetate in a solvent, the solution concentration being 0.1~0.5 mol / L; ii. Gelation: The sol prepared above is heated to 50-80°C and subjected to gelation reaction at a pH of 3-6 for 12-14 hours; iii drying and calcining: the gel prepared above was dried at 80 ~ 120 ℃, and then calcined at 500 ~ 950 ℃, the calcination time is 13-15 hours; iv. Post-treatment: subjecting the calcined product to plasma treatment, ultrasonic treatment or heat treatment to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the amine solution, control the addition amount and dispersibility, add surfactants and auxiliary additives, continue stirring and mixing, and obtain a nano-composite amine liquid decarbonizer.
[0018] In the present invention, the preparation of nano-scale zirconium oxide and lithium oxide adopts the sol-gel method, and the reaction temperature, time, concentration of reactants and other factors can be controlled during the preparation process, so that the preparation of nano-scale zirconium oxide and lithium oxide is efficient, controllable and repeatable, ensuring that the particle size and morphology of the prepared nano-scale zirconium oxide and lithium oxide meet the requirements, and the properties and performance of the nano-scale zirconium oxide and lithium oxide reach the best state.
[0019] Preparation of sol: The concentration of reactants is usually between 0.1 and 0.5 mol / L, and the type and proportion of solvents also need to be selected according to the properties and requirements of the reactants. The solvent is one or more combinations of acetone, ethanol, n-butanol, isopropanol, n-propanol, isobutanol, methanol, ethylene glycol, propylene glycol, dimethylformamide, ethyl acetate, benzene, and water. For example, zirconium acetate can be dissolved in solvents such as isopropanol, acetone, and n-propanol, and lithium acetate can be dissolved in solvents such as water and methanol. Taking zirconium acetate as an example, 0.2 mol / L of zirconium acetate can be selected to be dissolved in acetone.
[0020] Gelation: The reaction temperature is generally between 50 and 80°C, the reaction time is about 12-14 hours, and the pH value is usually between 3 and 6. By controlling these parameters, the desired particle size and morphology can be obtained. For example, zirconium acetate can be dissolved in acetone and heated to 60°C, and the gelation reaction can be carried out at a pH of 4 for 12-14 hours.
[0021] Drying and calcining: The drying temperature is generally between 80 and 120°C, and the time is about 12-14 hours, which can be adjusted according to the actual situation. The calcining temperature is generally between 500 and 950°C, and the time is about 13-15 hours. The atmosphere is usually air, nitrogen, hydrogen, etc. Taking zirconium acetate as an example, the gel can be dried at 80°C for 12-14 hours, and then calcined to 800°C in a nitrogen atmosphere and kept warm for 4 hours.
[0022] In particular, the nano-scale zirconium oxide and lithium oxide used in the present invention have specific morphology and dispersibility, and the preparation method thereof also includes a specific post-treatment process to ensure its stability and activity. These post-treatment processes include plasma treatment, ultrasonic treatment, heat treatment, etc. These treatment processes further improve the activity and stability of the nano-scale zirconium oxide and lithium oxide, making them more suitable for addition to the amine liquid decarburizer to optimize their performance and stability. For example, the plasma treatment is one or more combinations of plasma enhanced chemical vapor deposition, plasma enhanced arc deposition or plasma enhanced thermal atomic deposition.
[0023] In the present invention, the addition of nano-scale zirconium oxide and lithium oxide: the prepared nano-scale zirconium oxide and lithium oxide are added to the amine solution, and the addition amount and dispersibility are controlled. In the present invention, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:2~3, and the addition amount is 0.1~0.5 wt%. The control of dispersibility can be achieved by mechanical stirring, ultrasonic dispersion and the like. Among them, the frequency and time of ultrasonic dispersion can be adjusted according to specific needs, generally within the range of 20~40kHz, the time is 30~60 minutes, and a surfactant (such as sodium dodecylbenzene sulfonate, etc.) is added to the amine solution. The added nano-composite amine solution decarbonizer can be stored at room temperature and has long-term stability.
[0024] Through the above technical scheme, the nanocomposite amine liquid decarbonizer of the present invention can improve the performance and stability of the amine liquid decarbonizer, and improve its corrosion resistance, foaming resistance and oxidation resistance. At the same time, the decarbonizer can have higher decarbonization selectivity and absorption efficiency, and its decarbonization efficiency reaches more than 95%.
[0025] Compared with the traditional amine liquid decarbonizer, the nano composite amine liquid decarbonizer of the present invention has the following uniqueness and innovation: (1) The particle size of nano-zirconia and lithium oxide is controlled within the range of 10 to 50 nm, because small particles can increase the surface area and reaction activity, thereby improving selectivity and efficiency. Through appropriate surface treatment processes, the surface charge and hydrophilicity of nano-zirconia and lithium oxide can be controlled, thereby optimizing their dispersibility and stability in amine solution. The use of specific additives can control the aggregation state of nano-zirconia and lithium oxide, thereby avoiding their agglomeration and precipitation, and improving the stability of the amine solution decarbonizer. Through appropriate stirring and ultrasonic treatment and other processes, the dispersibility and stability of nano-zirconia and lithium oxide in the amine solution can be further improved, thereby improving its selectivity and decarbonization efficiency. The uniqueness and innovation of the present invention lies in using nano-zirconia and lithium oxide as additives for the amine solution decarbonizer, and controlling their morphology and dispersibility by optimizing the post-treatment process, thereby improving the decarbonization efficiency and reducing the cost.
[0026] (2) The synergistic effect of nano-zirconia and lithium oxide is achieved through structure-activity relationship. Nano-zirconia can act as a strong acid site to adsorb and decompose CO2, while nano-lithium oxide can act as a weak alkaline site to adsorb and remove CO2. At the same time, nano-zirconia can also adsorb and stabilize lithium oxide in the amine solution, thereby increasing the available alkalinity and stability in the amine solution and improving the decarburization efficiency and stability. Therefore, nano-zirconia and lithium oxide can work synergistically, give full play to their respective advantages, and improve the performance and efficiency of amine decarburizer. After adding amine solution, nano-zirconia and lithium oxide can be adsorbed on the surface of amine solution molecules, increasing the available alkalinity and activity of amine solution, thereby increasing the rate and efficiency of decarburization reaction. In addition, nano-zirconia and lithium oxide can also increase the thermal stability and durability of amine solution and extend the service life of amine solution. By optimizing the addition amount and dispersibility of nano-zirconia and lithium oxide, the performance and stability of amine solution decarburizer can be further improved, and the energy consumption and cost in the decarburization process can be reduced. Therefore, the uniqueness and innovation of the present invention lies in utilizing the synergistic effect of nano-sized zirconium oxide and lithium oxide to optimize the performance and stability of the amine liquid decarbonizer and improve its application value in the industrial decarbonization process. Implementation
[0027] The present invention is described in detail below in conjunction with embodiments, but is not limited to the contents described in the following embodiments. Example 1
[0028] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:2, the addition amount is 0.1 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer. Example 2
[0029] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:3, the addition amount is 0.1 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer. Example 3
[0030] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:2, the addition amount is 0.3 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer. Example 4
[0031] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:3, the addition amount is 0.3 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer. Example 5
[0032] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:2, the addition amount is 0.5 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer. Example 6
[0033] a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-scale zirconium oxide and lithium oxide is 1:3, the addition amount is 0.5 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirring and mixing are continued to obtain a nano-composite amine liquid decarbonizer.
[0034] Comparative Example 1 a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: 0.5 mol / L zirconium acetate was dissolved in 1:1 methanol and ethanol, and 0.5 mol / L lithium acetate was dissolved in methanol; ii. Gelation: The sol prepared above was heated to 60°C and subjected to gelation reaction at a pH of 4 for 12 hours; iii drying and calcination: the gel prepared above was dried at 80 ℃, and then calcined at 800 ℃, the calcination time was 13 hours, and the heat was kept for 4 hours; iv. Post-treatment: Plasma-enhanced chemical vapor deposition of the calcined product to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the alcohol amine solution, the mass ratio of nano-sized zirconium oxide and lithium oxide is 1:2, the addition amount is 1 wt%, and the dispersibility is controlled by ultrasonic dispersion, the ultrasonic frequency is in the range of 30~35kHz, the time is 40~50 minutes, and 0.05wt% of sodium dodecylbenzene sulfonate and 0.2wt% of sodium chloride are added at the same time, and stirred to obtain a composite amine liquid decarbonizer.
[0035] Comparative Example 2 Referring to Comparative Example 1, only nano-sized zirconium oxide was added, with an addition amount of 0.5 wt%.
[0036] Comparative Example 3 0.05 wt% of sodium dodecylbenzene sulfonate and 0.2 wt% of sodium chloride are added to the traditional alcohol amine liquid, stirred and mixed, and a composite amine liquid decarbonizing agent is obtained.
[0037] The decarburization experiments were conducted on the decarburization agents of the embodiment and the comparative example, and the CO2 absorption amounts are shown in Table 1.
[0038] Table 1 CO2 absorption .
[0039] It can be seen from the above comparative experiments that in the present invention, the mass ratio of nano-sized zirconium oxide to lithium oxide is 1:2-3, and the addition amount is 0.1-0.5 wt%. If excessive amounts of nano-sized zirconium oxide and lithium oxide are added, their dispersibility and stability may be affected, thereby reducing the selectivity and efficiency of the decarburizer.
[0040] The technical solution of the present invention is to add nano-scale zirconium oxide and lithium oxide to the amine solution to give it a specific morphology and dispersibility, thereby improving the performance and stability of the amine solution decarburizer. If only one of the nano-materials is added, the performance and stability of the amine solution decarburizer may be affected, and the advantages and effects described in the present invention cannot be achieved.
[0041] Compared with traditional amine liquid, the nanocomposite amine liquid decarbonizer of the present invention has better corrosion resistance, foaming resistance, oxidation resistance, higher decarbonization selectivity and absorption efficiency. In the industrial decarbonization process, traditional amine liquid is easily affected by factors such as oxidation, decomposition, corrosion, etc., which leads to the decline of decarbonizer performance and shortened service life. The nanocomposite amine liquid decarbonizer of the present invention utilizes the synergistic effect and excellent performance of nano-scale zirconium oxide and lithium oxide to improve the performance and stability of the amine liquid decarbonizer, thereby reducing the energy consumption and cost in the decarbonization process, and has higher economy and practicality.
Claims
1. A nano composite amine liquid decarbonizing agent, characterized in that: It contains the following components: a. Amine substances; b. Nano-sized zirconium oxide, with a particle size between 10 and 50 nm; c. Nano-scale lithium oxide, with a particle size between 10 and 50 nm; d. surfactant; e. Auxiliary additives.
2. The nanocomposite amine liquid decarbonizing agent according to claim 1, characterized in that The amine substance is selected from alcohol amine, ether amine, amide and cyclic amine; the surfactant is sodium dodecylbenzene sulfonate; and the auxiliary additives are sodium chloride and potassium chloride.
3. The nanocomposite amine liquid decarbonizing agent according to claim 1, characterized in that The mass ratio of nano-sized zirconium oxide to lithium oxide is 1:2~3, and the added amount of the two is 0.1~0.5 wt% of the total amount of the decarburizer.
4. The nanocomposite amine liquid decarbonizing agent according to claim 1 or 2, characterized in that The amount of surfactant added is 0.01~0.05 wt% of the total amount of the decarbonizer.
5. The nanocomposite amine liquid decarbonizing agent according to claim 1 or 2, characterized in that The amount of auxiliary additives added is 0.1~0.5 wt% of the total amount of decarburizer.
6. The nanocomposite amine liquid decarbonizing agent according to claim 1, characterized in that The viscosity of nanocomposite amine liquid decarbonizer is 20~100 mPa·s, and its solubility in water is 20~35 wt%.
7. A method for preparing a nano composite amine liquid decarbonizing agent, characterized in that The following steps are involved: a. Preparation of nano-scale zirconium oxide and lithium oxide: comprising the following steps: i. Preparation of sol: dissolving zirconium acetate and lithium acetate in a solvent, the solution concentration being 0.1~0.5 mol / L; ii. Gelation: The sol prepared above is heated to 50-80°C and subjected to gelation reaction at a pH of 3-6 for 12-14 hours; iii drying and calcining: the gel prepared above was dried at 80 ~ 120 ℃, and then calcined at 500 ~ 950 ℃, the calcination time is 13-15 hours; iv. Post-treatment: subjecting the calcined product to plasma treatment, ultrasonic treatment or heat treatment to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-scale zirconium oxide and lithium oxide to the amine solution, control the addition amount and dispersibility, add surfactants and auxiliary additives, continue stirring and mixing, and obtain a nano-composite amine liquid decarbonizer.
8. The preparation method according to claim 7, characterized in that The solvent is one or more combinations of ethanol, n-butanol, isopropanol, isobutanol, methanol, ethylene glycol, propylene glycol, dimethylformamide, ethyl acetate, and benzene.
9. The preparation method according to claim 7, characterized in that The plasma treatment is one or more combinations of plasma enhanced chemical vapor deposition, plasma enhanced arc deposition or plasma enhanced thermal atomic deposition.
10. The nanocomposite amine liquid decarbonizing agent according to claim 1, characterized in that The control of dispersibility is carried out by mechanical stirring and / or ultrasonic dispersion, wherein the frequency of ultrasonic dispersion is in the range of 20 to 40 kHz and the time is 30 to 60 minutes.
Citation Information
Patent Citations
High-dispersity nano-zirconia particles and method for preparing transparent dispersoid of high-dispersity nano-zirconia particles
CN108529674A
Preparation method and application of nano carbon dioxide trapping agent
CN112791707A
Inorganic oxide particle, inorganic oxide particle dispersion and preparation method thereof, and method for producing surface modifier
CN113474288A
Method of producing nanoporous metal oxide material
EP1840086A2
Fuel reformer catalyst and absorbent materials
US20050232858A1